ANALYSIS OF OPPORTUNITIES AND CHALLENGES FOR HUMAN RESOURCES IN THE DIGITAL ERA: A LITERATURE REVIEW - Anggraeni, Fahdianti; Rindaningsih, Ida (Academic Journal Research, 2025)
Objective: This study examines the opportunities and challenges in developing human resources in education within the digital era, focusing on enhancing the quality and technological competence of educational personnel. Method: A literature review was conducted to analyze existing studies on human resource development in education, particularly concerning the integration of digital technologies into teaching and administrative processes. Results: The review identifies opportunities, such as the use of technology to create engaging teaching materials, improve learning effectiveness, and enhance educational efficiency. However, significant challenges include financial limitations, inadequate technological infrastructure, and restricted internet accessibility, which hinder the full realization of these opportunities. Novelty: By synthesizing insights from diverse sources, this study highlights the dual nature of digital transformation in education. It underscores the urgent need for strategic investment in technological infrastructure and ongoing professional development to address these challenges, thereby contributing to a more resilient and adaptable educational workforce.